Is Aquaponics Beneficial in Terms of Fish and Plant Growth and Water Quality in Comparison to Separate Recirculating Aquaculture and Hydroponic Systems? - Atique, Faiqa; Lindholm-Lehto, Petra; Pirhonen, Juhani (Molecular Diversity Preservation International, 2022)
Aquaponics is a technique where a recirculating aquaculture system (RAS) and hydroponics are integrated to grow plants and fish in a closed system. We investigated if the growth of rainbow trout (Oncorhynchus mykiss) and baby spinach (Spinacia oleracea) would be affected in a coupled aquaponic system compared to the growth of the fish in RAS or plants in a hydroponic system, all systems as three replicates. We also investigated the possible effects of plants on the onset of nitrification in biofilters and on the concentration of off-flavor-causing agents geosmin (GSM) and 2-methylisoborneol (MIB) in rainbow trout flesh and spinach. For the fish grown in aquaponics, the weight gain and specific growth rates were higher, and the feed conversion ratio was lower than those grown in RAS. In spinach, there were no significant differences in growth between aquaponic and hydroponic treatments. The concentration of GSM was significantly higher in the roots and MIB in the shoots of spinach grown in aquaponics than in hydroponics. In fish, the concentrations of MIB did not differ, but the concentrations of GSM were lower in aquaponics than in RAS. The onset of nitrification was faster in the aquaponic system than in RAS. In conclusion, spinach grew equally well in aquaponics and hydroponic systems. However, the aquaponic system was better than RAS in terms of onset of nitrification, fish growth, and lower concentrations of GSM in fish flesh.
Keywords: biological filtration; integrated aquaculture; muscle lipids; off-flavors; salmonids; soilless culture